Affective Style, Humor Styles and Happiness - Thomas E. Ford; Katelyn A. McCreight; Kyle Richardson (Europe's Journal of Psychology, 2014)
The present study examined the relationships between dispositional approach and avoidance motives, humor styles, and happiness. In keeping with previous research, approach motives and the two positive humor styles (self-enhancing and affiliative) positively correlated with happiness, whereas avoidance motives and the two negative humor styles (self-defeating and aggressive) negatively correlated with happiness. Also, we found support for three new hypotheses. First, approach motives correlated positively with self-enhancing and affiliative humor styles. Second, avoidance motives correlated positively with self-defeating humor style, and third, the positive relationship between approach motives and happiness was mediated by self-enhancing humor style.